Insectes ravageurs des graines de légumineuses - Huignard, Jacques; Glitho, Isabelle; Monge, Jean-Paul; Régnault-Roger, Catherine (éditions Quae, 2011)
Using the concrete example of industrial and food crop legumes in West Africa, the authors reflect on the development of African agriculture in the context of sustainable development. They address exhaustively the biology of legume seed pests (bean weevils) and analyse the various methods of effective and environmentally-friendly control. The work expands on the Integrated Pest Management methods for the bean weevils, the main legume seed pests: simple, inexpensive and low-pollution methods.